The Relationship between Religion and State According to the Perspective of K.H. Zainal Arifin Abbas - Rizki Pristiandi Harahap; Syahrin Harahap; Hasan Bakti Nasution (Budapest International Research and Critics University, 2019)
In-depth study of the relationship between religion and the State (Politics) until now is considered to be very relevant, because until now and even in the future this issue has the potential to continue to have heated debates and could become the root of conflict from various groups, both at the level world countries, large institutions as well as in small communities in every corner of the village. Because the issue of both relation is still considered to be turbulent with diverse human understandings, K.H. Zainal Arifin Abbas, known as an Islamic politician and charismatic Islamic thinker from North Sumatra, negated that ideally the relationship between Religion and State should be integrated in each country, because according to him this relationship is interlocked, in religious teachings (Islam) teaches a lot of the concept of ethics in the state or (politics), then in carrying out political activities very much needed ethics or ways of doing politics.